2021
DOI: 10.1002/stem.3360
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction-Mediated Cell-Cell Interaction Between Transplanted Mesenchymal Stem Cells and Vascular Endothelium in Stroke

Abstract: We have shown previously that transplanted bone marrow mononuclear cells (BM-MNC), which are a cell fraction rich in hematopoietic stem cells, can activate cerebral endothelial cells via gap junction-mediated cell-cell interaction. In the present study, we investigated such cell-cell interaction between mesenchymal stem cells (MSC) and cerebral endothelial cells. In contrast to BM-MNC, for MSC we observed suppression of vascular endothelial growth factor uptake into endothelial cells and transfer of glucose fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Moreover, blocking the gap junction channel of MSCs reversed the VEGF uptake of BMVECs in vitro and in vivo. These results revealed cell-cell interaction between MSC and BMVECs through gap junction [36]. Previous studies have shown that VEGF stimulates angiogenesis and increases BBB permeability, promoting inflammatory responses following stroke [129,130].…”
Section: Stabilizing Morphology and Crosstalk Of Cellular Components Blood-brain Barrier 431 Brain Microvascular Endothelial Cellssupporting
confidence: 58%
See 3 more Smart Citations
“…Moreover, blocking the gap junction channel of MSCs reversed the VEGF uptake of BMVECs in vitro and in vivo. These results revealed cell-cell interaction between MSC and BMVECs through gap junction [36]. Previous studies have shown that VEGF stimulates angiogenesis and increases BBB permeability, promoting inflammatory responses following stroke [129,130].…”
Section: Stabilizing Morphology and Crosstalk Of Cellular Components Blood-brain Barrier 431 Brain Microvascular Endothelial Cellssupporting
confidence: 58%
“…The morphological enclosing of the entire cerebral microvascular system, by the terminal feet of astrocytes and their interactions with BMVECs through extracellular vesicles, determines the BBB properties [51][52][53]. In addition, astrocytes contribute to the stability of TJs through VEGF-mediated signal transduction [27,36], and regulating tissue inhibitors of metalloproteinases (TIMPs) [54].…”
Section: Structure Of Blood-brain Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…With the resurgence of phenotypic assays in drug discovery, the observations in these systems are often complex as recently shown by cell-cell interactions in stroke models ( Kikuchi-Taura et al, 2020 ; Takeuchi et al, 2020 ; Kikuchi-Taura et al, 2021 ) and understanding the nature of the PPIs using novel technologies will allow the scientific community to better understand and unveil therapeutically relevant aspects of such PPIs to treat a variety of human diseases.…”
mentioning
confidence: 99%